Design and Dynamics Research of Exoskeleton based on Flexible Knee Joint - Qiao Xueyu Zhao Yanjun Li Zhao Jia Bingqi Chen Miao (Jixie chuandong)
In order to balance the linear output of the exoskeleton power and the safety in the wearing process, a wearable flexible knee joint exoskeleton with two working modes of power assist and buffering is designed. Firstly, the parameter calculation and structural design of the knee bumper and whole machine model of the exoskeleton are carried out. Then, the dynamics analysis of the joint is carried out and the theoretical moment of the joint is calculated by Matlab. Finally, the calculated parameters and theoretical moments are substituted into Adams to simulate the exoskeleton under the two working modes. By comparing the simulation results with the human motion standard data, it is proved that the exoskeleton assist mode can basically meet the wearer's normal walking needs, and the buffer mode can buffer the rigid impact under sudden conditions. An important theoretical basis for the subsequent system control and prototype manufacturing is provided.